Modelling the growth and utilisation of kikuyu grass (Pennisetum clandestinum) under grazing. 1. Model definition and parameterisation - Herrero, Mario; Fawcett, R.H.; Silveira, V.; Busqué, J.; Bernués, A.; Dent, J.B. (Elsevier, 2000)
This paper describes a Tropical Pasture Simulator. This is a simple mechanistic model representing the growth of vegetative tropical pastures under rotational or continuous grazing with responses to N fertiliser, temperature and irradiance that can be used as a tool to study management options for the development of sustainable grazing systems. The model was derived as an adaptation of the `Hurley pasture models' which were originally designed to simulate the growth of ryegrass. The model incorporates the processes of light interception and photosynthesis, leaf area expansion; growth, ageing and senescence of plant tissues, recycling of substrates from senescing tissues, nitrogen uptake, mineralisation of soil organic N, N leaching and grazing. The paper discusses the main structure of the model, its components and the main adaptations required to simulate the growth of tropical pastures. The model was parameterised for kikuyu grass (Pennisetum clandestinum) growing in dairy systems in highland regions of Costa Rica. This paper also discusses the sensitivity of parameter values and the development of minimum parameter datasets for time and cost-effective implementation of the model.